1996
DOI: 10.1044/jshr.3901.76
|View full text |Cite
|
Sign up to set email alerts
|

Speech Production in People Who Stutter: Testing the Motor Plan Assembly Hypothesis

Abstract: The main purpose of the present study was to test the hypothesis that persons who stutter, when compared to persons who do not stutter, are less able to assemble abstract motor plans for short verbal responses. Subjects were adult males who stutter and age-and sex-matched control speakers, who were tested on naming pictures and words, using a choice-reaction time paradigm for both tasks. Words varied in the number of syllables (1, 2, and 3 syllables) and, for the bisyliabic words, also in the number of consona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
52
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 67 publications
4
52
1
Order By: Relevance
“…Rather, it is also possible that speech motor control/productive processes could contribute to these betweengroup differences, although not as the only factor accounting for the differences. Van Lieshout, Hulstijn, and Peters (1996), for example, suggested that atypical motor control in individuals who stutter is neither the sole cause nor sole factor to consider when studying the development of stuttering. Indeed, it is recognized that SRT is the end-product of several processes (e.g., cognitive + linguistic +motoric); however, in the present study we attempted to minimize between-condition differences in motoric demands while allowing linguistic differences to vary in known or prescribed ways.…”
Section: Cws Exhibit Slower Initiation Of Picture Namingmentioning
confidence: 99%
“…Rather, it is also possible that speech motor control/productive processes could contribute to these betweengroup differences, although not as the only factor accounting for the differences. Van Lieshout, Hulstijn, and Peters (1996), for example, suggested that atypical motor control in individuals who stutter is neither the sole cause nor sole factor to consider when studying the development of stuttering. Indeed, it is recognized that SRT is the end-product of several processes (e.g., cognitive + linguistic +motoric); however, in the present study we attempted to minimize between-condition differences in motoric demands while allowing linguistic differences to vary in known or prescribed ways.…”
Section: Cws Exhibit Slower Initiation Of Picture Namingmentioning
confidence: 99%
“…One reason that might account for not finding the inter action between word size and group effects in the study of Van Lieshout et al (1996) was the manipulation of word size, in particular for the picture-naming task. For that task, all three-syllable words were formed by adding grammatical suffixes to bisyilabic words to indicate a plural form of these 20f course, when the motor plan consists of more than a single word (stress-group), the muscle command preparation stage will also take more time because more units in the motor plan will Increase the time to search the short-term motor buffer (Levait, 1989; Sternberg et al, 1978).…”
mentioning
confidence: 99%
“…In addition, in the study of Peters et al (1989), word size was varied along a somewhat wider range con trasting monosyllabic words with three-to four-syllable words. So, it is possible that a wider range in number of syllables within a word than used in Van Lieshout et al (1996) would be more successful in eliciting the potential problems people who stutter may have in processing infor mation at the motor plan assembly stage.…”
mentioning
confidence: 99%
See 2 more Smart Citations